Implementasi Manajemen Farmasi di Apotek: Analisis Kesesuaian Penyimpanan Obat Berdasarkan Standar Pelayanan Kefarmasian - Irfan Kurniawan; Yani Pratiwi; Asyari Al Hutama Azis (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Healthcare facilities play an essential role, not only as a place for pharmacists to carry out pharmacy practice but also in ensuring the quality of medicines provided to the community. Therefore, the aspect of drug storage is a crucial factor that requires careful attention. If not managed in accordance with established standards, it may decrease drug effectiveness, accelerate deterioration, cause dispensing errors, and result in undetected drugs that are nearing or have already passed their expiration date. The objective of this study was to identify drug storage management in APP, APT, and APSJ in Makassar City and to analyze the level of conformity of these storage systems with Pharmaceutical Service Standards No. 73 of 2016. Data were collected through direct observation using a checklist and interviews. This study employed an observational method with a descriptive quantitative and evaluative approach, which involved observing ongoing activities and comparing them with the regulations related to pharmaceutical service standards, particularly regarding drug storage management. The collected data were analyzed using descriptive assessment categories, where scores of 81–100% were classified as “very good,” 61–80% as “good,” 41–60% as “fair,” 21–40% as “poor,” and 0–20% as “very poor.” Based on the observations, the drug storage systems in APP, APT, and APSJ in Makassar City achieved scores of 90.48%, 90.91%, and 90.91%, respectively. These results fall into the “very good” category, indicating compliance with the Technical Guidelines for Pharmaceutical Services issued in 2019.